Preserving Hanoi's Architectural And Landscap Heritage (Hanoi : Xay dung, 1999)
The goal of this brochure is to offer a glimpse of Hanoi's architectural and landscap heritage dating from before1945.
Keywords: Architectural; Landscap Heritage; Hanoi; Architectural And Landscap Heritage -- Hanoi (Vietnam)